Development of Outbound Activities to Embed The Values of Character Education Through Interactive Multimedia (Department of Physical Education, Sport, Health and Recreation, 2018)
The purpose of this research and development is to generate outbound activities to instill the values of character education through interactive multimedia for participants of nature lovers extracurricular. The design of this study uses a research and development model from Lee and Owens. The results of research and development of large group trials on 45 participants resulted in 86.18% percentage of product validation and 90% results from product effectiveness.The conclusion of this research and development is the product is valid with very good category and well used as training media.